PHYTOCHEMICAL SCREENING, TOTAL PHENOLIC CONTENT, AND ANTIOXIDANT ACTIVITY OF WATER, ETHYL ACETATE, AND N-HEXANE FRACTIONS FROM MISTLETOE MORINGA OLEIFERA LAM. (DENDROPHTHOE PENTANDRA (L.) MIQ.) - Kristiningrum, Nia; Wulandari, Lestyo; Zuhriyah, Aini (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was to investigate the phytochemical screening, total phenolic content (TPC), and antioxidant activity of fractions of water, ethyl acetate, and n-hexane from Dendrophthoe pentandra (L.) Miq. and mistletoe of Moringa oleifera Lam. Methods: Simplicia extracted with 96% ethanol using maceration method. Liquid-liquid extraction was used for fractionation with water, ethyl acetate, and n-hexane as solvent. Phytochemical screening, determination of TPC, and antioxidant activity were performed against these fractions. Antioxidant activity was determined by 2,2-diphenyl-1-picrylhydrazyl method. The TPC was measured by Folin–Ciocalteu reagent and use gallic acid (GA) as a standard. Results: Water fraction contains saponin and polyphenols. Ethyl acetate fraction contains alkaloids, flavonoids, saponins, terpenoids, and polyphenols. N-hexane fraction only contains alkaloids and terpenoids. The TPC and antioxidant activity of fractions of water, ethyl acetate, and n-hexane were 9.42±1.16%, 21.35±1.86%, and 67.40±0.82% mg GA equivalent/g fraction and 29.46 μg/ml±0.99%, 7.08 μg/ml±0.39%, and 10.90 μg/ml±1.05%, respectively. Conclusion: Fraction of ethyl acetate exhibited the highest antioxidant activity and TPC. This study showed that there were significant correlations between TPC and antioxidant activity at significance level p<0.05.